Multiple mediation effects of health locus of control and hope on the relationship between stroke patients' social support and self-management - Lei Ting-Ting; Han Hong-Mei; Liu Xiao-Jing (Sciendo, 2020)
This study aimed to identify the mediation effects of health locus of control (HLC) and hope between stroke patients' social support and self-management.